1990
DOI: 10.1073/pnas.87.9.3454
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptors activate Ca2+ mobilization and Ca2+ influx into astrocytes.

Abstract: We measured changes in the molar concentration of cytosolic Ca2' ([Ca2+1]) in individual astrocytes in culture produced by the glutamate analog quisqualate (QA) and related substances by using fura-2 digital fluorescence microscopy. In cells cultured from the cortex, hippocampus, and cerebellum, the QA analog a-amino-3-hydroxy-5-methyl-isoxaiole-4-propionate (AMPA; 10 ,uM) produced a slow increase in [Ca2J11 that was modest in amplitude (-200 nM). These effects were completely abolished by 10 ,IM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
135
2
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(150 citation statements)
references
References 34 publications
(31 reference statements)
9
135
2
4
Order By: Relevance
“…40 -42 Subsequent in vitro experiments have demonstrated that glial cells express the very same diverse variety of neurotransmitter receptors and ion channels as do neurons, [43][44][45][46][47][48][49][50][51][52][53][54][55] thus raising the question of the role for neuroglia in information processing in the brain. Further experiments have found that the expression pattern of neurotransmitter receptors in situ is very much restricted by the immediate neurotransmitter environment; as a consequence glial cells are properly endowed to sense the neurotransmitters released in their territorial domains.…”
Section: Signaling In Neuronal-glial Circuits 1) Glial Cells Express mentioning
confidence: 99%
“…40 -42 Subsequent in vitro experiments have demonstrated that glial cells express the very same diverse variety of neurotransmitter receptors and ion channels as do neurons, [43][44][45][46][47][48][49][50][51][52][53][54][55] thus raising the question of the role for neuroglia in information processing in the brain. Further experiments have found that the expression pattern of neurotransmitter receptors in situ is very much restricted by the immediate neurotransmitter environment; as a consequence glial cells are properly endowed to sense the neurotransmitters released in their territorial domains.…”
Section: Signaling In Neuronal-glial Circuits 1) Glial Cells Express mentioning
confidence: 99%
“…Astrocytes, a sub-type of glial cells present in the CNS, express the receptor for Glu. Upon binding of Glu, membrane-bound ion channels open immediately, promoting Ca 2+ influx [27][28][29] . Therefore, astrocytes represent an ideal system to monitor Glu activation of cells using real-time single-cell ratiometric Ca 2+ imaging.…”
mentioning
confidence: 99%
“…However, it remained to be determined whether [Ca 2~] 1 oscillations are induced in native neural cells by activation of mGluR5. Several studies have indicated that glutamate elicits oscillatory [Ca 2~] 1responses in cultured astrocytes through [Ca 2~]mobilization (Cornell-Bell et al, 1990a;Glaum et al, 1990;de Barry et al, 1991;Holzwarth et al, 1994). It has also recently been reported that mGluR5 is preferentially expressed in cultured astrocytes and that this expression is up-regulated by specific growth factors such as basic fibroblast growth factor (bFGF), epidermal growth factor (EGF), and transforming growth factor-a (TGF-a) (Miller et al, 1995).…”
mentioning
confidence: 99%